Reliability of a self-reported health questionnaire in a periodontal disease study - Ho, Alex W.; Grossi, Sara G.; Dunford, Robert G.; Genco, Robert J. (Journal of periodontal research, 1997)
This study assesses the reliability of a self‐reported health questionnaire completed by 413 subjects aged 25–74 yr in the Erie County Periodontal Disease (ECPD) Study. Specific questions on general and oral health conditions were completed by each subject during a first visit and at a follow‐up examination 2 yr later, and the two compared. Results showed that the overall measure of agreement between the two visits is substantial (average kappa, k=0.80). Variation by gender and age were minimal. Questions regarding allergy to medications, oral treatment, reason for tooth extraction, health symptoms and history of systemic diseases exhibited high levels of agreement (kappa ranged from 0.71–0.90). Information on vitamin and mineral intake yielded k= 0.63. Oral conditions scored the lowest but were still acceptable (k= 0.57). These findings indicate that there were no significant discrepancies in self‐reported responses to the health questionnaire used in the ECPD Study. Although the information provided by the subject may not be as accurate as compared to laboratory testing, it is nevertheless a reliable source of information which can be utilized cost‐effectively in research studies.